2015
DOI: 10.1186/s12916-015-0419-z
|View full text |Cite
|
Sign up to set email alerts
|

The variable phenotype and low-risk nature of RAS-positive thyroid nodules

Abstract: BackgroundOncogenic mutations are common in thyroid cancers. While the frequently detected RAS-oncogene mutations have been studied for diagnostic use in cytologically indeterminate thyroid nodules, no investigation has studied such mutations in an unselected population of thyroid nodules. No long-term study of RAS-positive thyroid nodules has been performed.MethodsWe performed a prospective, blinded cohort study in 362 consecutive patients presenting with clinically relevant (>1 cm) thyroid nodules. Fine need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 32 publications
4
47
2
Order By: Relevance
“…All NIFTPs that were sent for targeted mutation analysis harbored RAS mutations. The findings of RAS mutations in NIFTPs is consistent with the literature, which documents the prevalence of RAS mutations in follicular‐patterned tumors …”
Section: Discussionsupporting
confidence: 90%
“…All NIFTPs that were sent for targeted mutation analysis harbored RAS mutations. The findings of RAS mutations in NIFTPs is consistent with the literature, which documents the prevalence of RAS mutations in follicular‐patterned tumors …”
Section: Discussionsupporting
confidence: 90%
“…Prior to the change in nomenclature, a prospective study by Medici et al analyzed the behavior of RAS‐positive thyroid nodules. All RAS‐positive malignancies in their cohort demonstrated very low‐risk characteristics . They were diagnosed as FVPTC with no evidence of capsular or lymphovascular invasion, extrathyroidal extension, or metastases.…”
Section: Discussionmentioning
confidence: 99%
“…They were diagnosed as FVPTC with no evidence of capsular or lymphovascular invasion, extrathyroidal extension, or metastases. It is likely that many of these neoplasms would now be described as NIFTP . Paulson et al also conducted a study to review the slides of previously diagnosed FVPTC and determine how many met criteria for NIFTP.…”
Section: Discussionmentioning
confidence: 99%
“…The PPV is expected to decrease for all currently available molecular tests, as NIFT-P was considered a malignant neoplasm in the validation studies and subsequent studies. For instance, in a recent study, Medici et al 51 found that 17 of the 362 thyroid nodules were RAS-positive by miRInform Thyroid molecular test. The results showed that 7 of 10 RAS-positive resected nodules represented NIFT-Ps.…”
Section: Other Molecular Tests For Thyroid Cancermentioning
confidence: 99%